Innovation in Curriculum Design and Assessment: A Field Study in Secondary Schools in the City of Sétif - YAHIAOUI, Abdelkarim; BENGUESSMIA, Farid (Journal of Human Sciences, 2025)
The researchers conducted a study on the impact of using technology in curriculum design and assessment on student performance in high schools in the city of Setif for the academic year (2023/2024). They selected a sample of 200 high school students and divided them into two groups: a group that uses technology in education and a group that relies on traditional methods. After collecting and analyzing the data, the results of the study concluded that using technology in curriculum design and assessment has a positive impact on student performance in high schools in the city of Setif.